Problems or prospects? Being a parent in the early phase of the COVID-19 pandemic in Germany - Ecker, Angelika; Jarvers, Irina; Schleicher, Daniel; Kandsperger, Stephanie; Schelhorn, Iris; Meyer, Marie; Borchert, Thomas; Lüdtke, Michael; Shiban, Youssef (Frontiers in Psychology, 2022)
Background In the early phase of the COVID-19 pandemic, many restrictions hit people in ways never seen before. Mental well-being was affected and burden was high, especially for high-risk groups such as parents. However, to our knowledge no research has yet examined whether being a parent was not only a risk for psychological burden but also a way to cope with the COVID-19 pandemic. Method An online survey was used to collect data from 1,121 participants from April to June 2020. In addition to demographic variables, risk factors (financial burden, problems complying with COVID-19 restrictions, and pre-treatment due to mental health problems) and protective factors (emotion regulation, humor, and crisis self-efficacy) were collected. The dataset was divided into three groups: parents whose children lived at home (n = 395), parents whose children did not (no longer) live at home (n = 165), and people who were not parents (n = 561). Results A linear mixed effect model showed that parents had no higher burden than non-parents, and even less when children did not live at home. Expected risk factors were generally less important, and there were no differences between parents and non-parents. In contrast, parents had advantages in protective factors. Conclusion In the early phase of the COVID-19 pandemic, it was shown that parents (with and without their children at home) were not necessarily at risk due to additional burden, but also had prospects of coping better with the situation than people without children.